Improvised infrastructure and redistributive rights: Informal public transport in an Indonesian city. Issue 5 (3rd September 2022) - Peters, Robbie
Abstract: Through a study of the motorbike-taxi drivers of the present and the minibus drivers of the past in Indonesia, I discuss how an improvised public transport infrastructure funded by the household fills the gaps left by a heavy transport infrastructure funded by the state and corporate capital. I argue that improvised infrastructure is built and maintained by the underemployed majority through their survival strategy of crowding—or bringing the city together in one place. As such, it is a collective project that takes advantage of multiple horizontal alliances across the city. It is also a political project that redresses the maldistribution and malfunctioning of heavy infrastructure through a downward redistribution of transport and communications technologies. Through the lens of improvised public transport in the sprawling Indonesian port city of Surabaya, I elaborate on these ideas to show how redistribution is only possible through strategies of tinkering and unaccountability—strategies that enable the underemployed to use infrastructure on their terms and to profit from it.